(untitled) (Journal of Global Accounting, 2024)
The objective of this study was to examine the effect of board characteristics on the firm performance of conglomerates listed on the Nigerian Exchange Group (NGX). The study specifically examined the effect of board size, audit committee size and board gender diversity on the performance of conglomerates firms in Nigeria. The study adopted the ex-post facto research design because the event under investigation had already taken place. The population of the study was made up of 5 conglomerates listed on the Nigerian Exchange Group. The sample size was same as the population. Descriptive statistics such as mean and standard deviation were used in describing the nature of the data while ordinary least square regression was used to validate the hypotheses. The results showed that: Board Size has positive non-significant effect on the return on assets; Audit Committee Size has negative significant effect on the return on assets; and Board Gender Diversity has negative significant effect on the return on assets of conglomerate firms in Nigeria. Based on these findings, the study recommended that: conglomerates can increase on the size of the board, or decreases based on other reasons other than profitability, the firms in the study should strive to reduce the size of their audit committees as it will help in cutting costs, and channeling the needed funds into various areas of productivity within the organization.